Corrective physical exercise program for patients with idiopathic scoliosis/Programa de ejercicios físicos correctivos para pacientes con escoliosis idiopática - Reinaldo Benítez López; Jorge de Lázaro Coll Costa; Ardy Rafael Rodríguez García; Luis Rene Quetglas González; Nélida Moraima Machín Quiñonez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The problem of the study lies in the fact that the treatments for children with scoliosis in Chile lack integration from physical exercise. The objective was to analyze physical exercise for the treatment of children with idiopathic scoliosis. The various forms of physical treatment in idiopathic scoliosis were studied through the review of official documents (patient medical records, exercise programs and intervention methods). The research was carried out at the Cuban Center for Physical Rehabilitation in Temuco, Chile. The indirect or non-interactive empirical method was applied: analysis of official documents, analysis-synthesis and modeling, which allowed the theoretical systematization of physical exercise in treatment. As a fundamental result, the program for the treatment of idiopathic scoliosis is designed through corrective physical exercises in a period of 18 months.